The limitations of a ‘high-risk’ approach for the prevention of dental caries - Batchelor P, Sheiham A. (Blackwell Synergy, 2002)
The decline in the prevalence of caries has lead several authors to advocate the adoption of a ‘high-risk’ approach for caries preventive strategies. This paper analyses such an approach.